Central Precocious Puberty in a Three-Year-Old Girl - Suryani Jamal; Liong Boy Kurniawan; Suci Aprianti; Ratna Dewi Artati; Ruland DN Pakasi; R Satriono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Precocious puberty is defined as the onset of secondary sexual characteristics before 8 years of age in girls and 9 years in boys. Central Precocious Puberty (CPP) is caused by early activation of the hypothalamic-pituitary-gonadal axis. Laboratory test of LH, FSH, and Estradiol is recommended for monitoring suppressive effects from GnRHa therapy in the early three months and every six months. This study aimed to report a case of CPP in a 3-year and 3-month-old girl. A 3-year and 3-month-old girl went to the hospital with vaginal bleeding (menstruation), breast development, and pubic and axilla hair for 7-month-old. Physical examination found moderately ill with obesity, body weight 20 kg, height 98 cm. Tanner stage was A2M3P2, café au lait was found in the left forehead with size 7x3.5 cm. In March 2015 before GnRHa therapy, LH, FSH and Estradiol level increased with levels of 4.32 mlU/mL, 6.01 mlU/mL, and 67 pg/mL, and after 3 months of the treatment was 0.87 mlU/mL, 2.51 mlU/mL and <20 pg/mL. Pelvic ultrasonography showed suggestive precocious puberty, bone age 5-year and 9-month (Greulich and Pyle), CT-Scan of the brain showed hypothalamic tumor suspected hypothalamic hamartoma. This patient was treated with a GnRHa injection every 4 weeks. Leuprorelin is a synthetic non-peptide analogue of natural GnRH. The diagnosis was based on medical history, physical examination, laboratory, and radiological findings. The prognosis of the patient was good.